Prevalence of odontogenic cysts and tumors associated with impacted third molars: A systematic review and meta-analysis. Issue 6 (June 2019) - Mello, Fernanda Weber; Melo, Gilberto; Kammer, Pedro Vitali; Speight, Paul M.; Rivero, Elena Riet Correa
Abstract: Purpose: This systematic review aimed to investigate the prevalence of odontogenic cysts and tumors associated with impacted third molars (ITM). Methods: Only studies that performed histopathological diagnosis of lesions were eligible for inclusion. Five main electronic and three grey literature databases were searched. Risk of bias (RoB) of included articles was assessed using the Joanna Briggs Institute Critical Appraisal Checklist for Studies Reporting Prevalence Data. Results: From 1, 300 studies identified, 16 met the inclusion criteria. Seven studies were classified as high, seven as moderate, and two as low RoB. The prevalence of odontogenic cysts and tumors associated with ITM was 5.3% (95%CI: 3.1%–8.1%) of ITM. Odontogenic cysts in particular were found in 4.4% (95%CI: 2.5–6.8%) of the extracted ITM, whilst odontogenic tumors in 0.5% (95%CI: 0.2–0.9%). The dentigerous cyst was mentioned in eleven studies with a pooled prevalence of 2.1% (95%CI: 1.4–3.1%). The odontogenic keratocyst was cited by nine studies and had a prevalence of 0.5% (95%CI: 0.2–0.7%). The radicular cyst was mentioned only in three articles and the pooled prevalence was 4.7% (95%CI: 0.0–19.4%) Conclusion: Odontogenic cysts and tumors were found in 5.3% of ITM extracted. The most common lesions were the radicular cyst, dentigerous cyst, and odontogenic keratocyst.